2020
DOI: 10.1371/journal.pone.0229404
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of disability among adults with chronic obstructive pulmonary disease, Behavioral Risk Factor Surveillance System 2016–2017

Abstract: Background The prevalence of disabilities is rising steadily, reflecting an aging population and an increasing burden of chronic conditions affecting quality of life. There are scant national data on the prevalence of disability among individuals with chronic obstructive pulmonary disease (COPD). The main objective was to estimate the prevalence of common disabilities among US-based individuals diagnosed with COPD. Methods Data from the BRFSS, a national telephone survey examining health-related behaviors in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Prevalence of debility was also noted to be higher among middle-aged adults participating in recent US Behavioral Risk Factor Surveillance System surveys. 57 Higher middle-aged prevalence of debility and frailty is also consistent with the fact COPD ranks third among leading causes of disability-adjusted life-years in the United States, and eleventh in terms of total years lived with disability. 58 Middle-aged COPD patients are also known to have substantially increased healthcare cost and decreased work productivity.…”
Section: Discussionsupporting
confidence: 55%
“…Prevalence of debility was also noted to be higher among middle-aged adults participating in recent US Behavioral Risk Factor Surveillance System surveys. 57 Higher middle-aged prevalence of debility and frailty is also consistent with the fact COPD ranks third among leading causes of disability-adjusted life-years in the United States, and eleventh in terms of total years lived with disability. 58 Middle-aged COPD patients are also known to have substantially increased healthcare cost and decreased work productivity.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, healthcare practitioners should facilitate caregiver attendance at follow-up appointments, so that their unique perception of the health of the patient can be discussed [ 99 ]. As COPD is associated with substantial cognitive, mobility, and auditory disability [ 100 ], a holistic approach to preventive care, smoking cessation, pulmonary rehabilitation, and patient and caregiver education that extends beyond exacerbation management should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it seems that having a pet can offer both psychological and physical health benefit decreasing both sedentary lifestyle and levels of functional limitation [ 82 ]. In women with COPD, one of the reasons behind this could be the fact that women’s health is often ignored due to gender disparity; also, females with COPD experience a greater risk of exacerbation and more severe symptoms than men, producing severe stages of COPD and generating a higher prevalence of functional limitation [ 25 , 60 ]. In the current study, the prevalence of functional limitation increased over time in obese women with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…This consequently affects their ability to complete both daily life activities, such as dressing, stair climbing and household chores, and more complex tasks known as instrumental activities of daily living, such as shopping, housework and using public transport and individuals suffering from COPD face a difficult process of adaptation to their health condition [ 22 ]. Even though a number of studies have pointed out that the most widely recognized conditions causing functional limitations among people are rheumatoid arthritis, spine issues and cardiovascular disease and that these conditions increase in prevalence as the population ages [ 23 , 24 ], Djibo et al [ 25 ] reported that the highest rates of functional limitation occur in middle-aged adults (45–64 years old) with COPD, although the reasons for this finding are not completely understood. In fact, patterns of functional limitation in activities of daily living and related determinants, specifically in COPD patients, are currently under investigation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%